Prevalence of doping in sports: doping control in Norway, 1977-1995 - Bahr, R.; Tjornhom, M. (Clinical Journal of Sport Medicine, 1998)
OBJECTIVE: To examine the results from doping controls conducted by the Norwegian Confederation of Sport (NCS) from 1977 to 1995. METHODS: Data were collected by combining three computerized databases and manual records on samples taken and results from analyses in the International Olympic Committee (IOC)-accredited laboratories in London, Huddinge, Cologne, and Oslo. Samples were declared positive if they contained any banned substance on the IOC list that was in effect at any given time. RESULTS: A total of 15,208 samples were taken; most of them (12,870; 85%) were from Norwegian athletes (90% unannounced tests) belonging to national federations under NCS jurisdiction (NCS members), 461 (3%) were from external Norwegian athletes (either users of private gyms or athletes in organized sports federations not affiliated with the NCS), and 1,874 (12%) were from foreign athletes (three cases with unknown affiliation). There were 130 positive samples and 24 refusals among NCS members (1.2%; men, 1.4%; women, 0.3%), 86 positive samples and 8 refusals among external Norwegian athletes (20%; men, 24%; women, 8%), and 39 positive samples and 1 refusal among foreign athletes (1.6%; men, 2.1%; women, 0.7%). A gradual decrease in the percentage of positive samples was observed among NCS members as testing frequency was increased gradually from 1987 to 1995 in the three high-prevalence sports: powerlifting, weightlifting, and athletics. CONCLUSION: An increase in the test frequency of doping tests was associated with a decrease in the percentage of positive samples in targeted sports.